2018
DOI: 10.1242/dmm.030056
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a double binary transgenic zebrafish model to study myeloid gene regulation in response to oncogene activation in melanocytes

Abstract: A complex network of inflammatory genes is closely linked to somatic cell transformation and malignant disease. Immune cells and their associated molecules are responsible for detecting and eliminating cancer cells as they establish themselves as the precursors of a tumour. By the time a patient has a detectable solid tumour, cancer cells have escaped the initial immune response mechanisms. Here, we describe the development of a double binary zebrafish model that enables regulatory programming of the myeloid c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Subsequent zebrafish studies have shown a similarly rapid recruitment of neutrophils and/or macrophages to the skin, liver and brain in response to transgenic expression of numerous oncogenes, e.g. HRAS G12V , KRAS G12V , NRAS Q61K , Src, Xmrk, Myc and Akt [6,7,[39][40][41]60,68,104,[140][141][142][143]. Live imaging has provided insight into the dynamics of the intrinsic inflammatory response following tumour initiation within these models.…”
Section: Zebrafish Studies Reveal Leukocyte Recruitment and Trophic Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent zebrafish studies have shown a similarly rapid recruitment of neutrophils and/or macrophages to the skin, liver and brain in response to transgenic expression of numerous oncogenes, e.g. HRAS G12V , KRAS G12V , NRAS Q61K , Src, Xmrk, Myc and Akt [6,7,[39][40][41]60,68,104,[140][141][142][143]. Live imaging has provided insight into the dynamics of the intrinsic inflammatory response following tumour initiation within these models.…”
Section: Zebrafish Studies Reveal Leukocyte Recruitment and Trophic Fmentioning
confidence: 99%
“…Transcriptomic analysis of PNC-associated neutrophils in an NRAS Q61K melanoma model, showed upregulation of genes that correspond with growth-and invasion-promoting properties, e.g. FGF-1 and -6, cathepsin-H and galectin1 -and -3 [60].…”
Section: Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that in vivo biotinylation in skeletal muscle cells requires biotin supplementation in the zebrafish embryo media [26]. However, biotin supplementation has not been necessary in a number of tissues in which biotagging has been performed [31,44,45]. The differences in endogenous levels of biotin may be due to variations in maternal diet.…”
Section: Balance Between Avi Effector and Bira Levelsmentioning
confidence: 99%
“…Buoyed by this important finding, Ac/Ds elements were employed to facilitate the integration of a reporter construct into the zebrafish genome with high efficiency, leading to remarkable germline transmission rates (Emelyanov et al, 2006). This approach was the integration method of choice used to generate transgenic zebrafish lines for the chemical-inducible LexPR transactivation system (Emelyanov and Parinov, 2008, Kenyon et al, 2018), as well as for a systematic mutagenesis gene-trapping screen (Quach et al, 2015). While these studies demonstrated the utility of Ac/Ds as an efficient method for propagation of transgenes through the germline, they overlooked its strong potential for transient expression of DNA elements in F 0 embryos, which is a current limitation of the zebrafish model.…”
Section: Introductionmentioning
confidence: 99%